CERVICAL CANCER EPIDEMIOLOGY IN UZBEKISTAN (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
According to the World Health Organization, in Uzbekistan, as in the rest of the world, cervical cancer is the second most common cancer after breast cancer among women of all ages. Cervical cancer is the second leading cause of death among women of childbearing age (18-45 years) after breast cancer.